2020
DOI: 10.1093/jme/tjaa094
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Tick Surveillance and Control Practices in the United States

Abstract: Tickborne diseases are an increasing public health threat in the United States. Prevention and diagnosis of tickborne diseases are improved by access to current and accurate information on where medically important ticks and their associated human and veterinary pathogens are present, their local abundance or prevalence, and when ticks are actively seeking hosts. The true extent of tick and tickborne pathogen expansion is poorly defined, in part because of a lack of nationally standardized tick surveillance. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…Additionally, results revealed that federal Land Management and a trail's Elevation Gain both were significantly associated with the number of Tick Presence Reviews. Given that others have indicated that sub-state level (municipal, county) governmental entities may need increased support for tick and pathogen surveillance [14], the association with Tick Presence Reviews identified here instead reinforces the crucial role of federal land management agencies in tick surveillance and control practices. However, the association between private land management-frequently under the control of a local land trust-and Tick Presence Reviews warrants further investigation.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Additionally, results revealed that federal Land Management and a trail's Elevation Gain both were significantly associated with the number of Tick Presence Reviews. Given that others have indicated that sub-state level (municipal, county) governmental entities may need increased support for tick and pathogen surveillance [14], the association with Tick Presence Reviews identified here instead reinforces the crucial role of federal land management agencies in tick surveillance and control practices. However, the association between private land management-frequently under the control of a local land trust-and Tick Presence Reviews warrants further investigation.…”
Section: Discussionmentioning
confidence: 58%
“…We believe this research represents a low-cost and promising tool for identifying specific recreational trails that warrant more robust active surveillance, particularly at locations that may be under-surveilled, like municipal and county locations [14] as well as those managed by private institutions, such as local land trusts. Furthermore, despite the online and voluntary nature of data collected, identification of ticks at nearly 10% of trails can be contextualized within comparable research; in a study examining presence of Ixodes scapulari along more than 900 km of the Appalachian trail from West Virginia to Vermont, ticks presence was indicated at 21 (4.3%) of actively surveilled sites (N = 489) [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even minor changes in land use can affect the spread of other vectors, such as Culex mosquitoes, thereby increasing the potential incidence of West Nile virus and other mosquito‐borne pathogens (Bowden et al 2011). Given this dynamic situation, accidental tick introductions (Hutcheson et al 2019), and a recognition that tick distribution maps are outdated (James et al 2006, Estrada‐Peña et al 2018, Eisen and Paddock 2020), it is important to identify and document current tick populations and their associated pathogens (Mader et al 2020). Change is expected to continue to occur, and it has been hypothesized that the range of Dermacentor variabilis (American dog tick) could expand by 50% in response to climate change (Sonenshine 2018).…”
Section: Introductionmentioning
confidence: 99%